Assessing the Therapeutic Role of Oral Gastrografin in Subacute Intestinal Obstruction - Zubair, Muhammad; Noman, Syed Muhammad; Nasir, Ammad ud Din; Malik, Arsalan Sharif; Naz, Faheem Ullah; Ramzan, Amna (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the therapeutic role of gastrografin in patients with subacute intestinal obstruction.Study Design: Quasi-experimental study.Place and Duration of Study: Surgical Department, Combined Military Hospital, Rawalpindi, Pakistan from Jul to Dec 2019.Methodology: A total of 112 patients who presented to Combined Military Hospital, Rawalpindi with subacute intestinal obstruction were included. Fifty-six patients were each allotted into group-A and group-B. Group-A were controls and received conventional treatment, whereas group-B, which was the study group received addition of 100 ml gastrografin meal. Patients were followed up with variables like operative rates, hospital stay during the admission and further readmissions with similar complaints were also assessed in next 3months time.Results: Surgical operation was performed in 14(25%) of the non-gastrografin group (group-A), for whom conservative treatment failed. In contrast, surgery was required in 5(8.9%) patients from the gastrografin group (group-B). The length of hospital stay showed a significant reduction from 5.02±1.61 days to 3.2±0.72 days for groups A and B, respectively. Readmission rate between groups was not statistically significant (p=0.151).Conclusion: We concluded that the gastrografin administration in subacute intestinal obstruction has a definite advantage in terms of lower surgery rate and reduced hospital stay.